Measurement of the [omega] 0c baryon lifetime - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; Kolpin, Michael; et al. (Physical review letters, 2018)
We report a measurement of the lifetime of the Ω0c baryon using proton-proton collision data at center-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment. The sample consists of about 1000 Ω−b→Ω0cμ−¯νμX signal decays, where the Ω0c baryon is detected in the pK−K−π+ final state and X represents possible additional undetected particles in the decay. The Ω0c lifetime is measured to be τΩ0c=268±24±10±2 fs, where the uncertainties are statistical, systematic, and from the uncertainty in the D+ lifetime, respectively. This value is nearly four times larger than, and inconsistent with, the current world-average value.
Im Titel ist Omega als griechischer Buchstabe dargestellt
Im Titel sind "0" und "c" untereinander geschrieben: "0" hochgestellt, "c" tiefgestellt
R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere] (LHCb Collaboration)
Gesehen am 29.05.2019